The glass queen - Showalter, Gena (Showalter, Gena. Forest of good and evil, 2020)
"Ashleigh Ansklelisa may be called the Glass Princess due to her weak heart, but Saxon, king of the Avian, knows she is more dangerous than broken glass, in this Cinderella retelling that sweeps readers into the magical land of Enchantia, filled with treacherous enemies, unexpected allies, forbidden love, and dangerous magic! Can destined lovers find their way to each other, or will evil win the day? Everything changes at the stroke of midnight as one determined princess fights for her legacy, her love, and the crown that is her destiny" --